The Effectiveness of public International Law in Combating Maritime Piracy - Hamed Mohamed Farag, Assist. Prof. Dr. Mohamed (Basra studies journal, 2023)
Piracy constitutes an attack on the principle and freedom of navigation, that original principle called for by all international norms, foremost of which is the Islamic Sharia through its clear texts covering all aspects of life, and countries have agreed to fight this crime and punish its perpetrator, until the international custom has settled on considering the pirate an enemy of the race Good news, because of its actions directed against the entire international community, and its cause of many dangers that threaten lives as well as international trade and dealings between members of the international community, and every country tries to ensure its legislation protects and deters these crimes in addition to the international efforts made in this regard.